Reconsider the lowly bug - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Have you ever eaten insects? Some people find the idea revolting, while others consider certain insects a gustatory delight. Insects make up a large proportion of the world's biomass - indeed, scientists don't even know how many species exist,...